Spin-glass polyamorphism induced by a magnetic field in LaMnO3 single crystal. (20th April 2018) - Eremenko, V V; Sirenko, V A; Baran, A; Čižmár, E; Feher, A
Abstract: We present experimental evidence of field-driven transition in spin-glass state, similar to pressure-induced transition between amorphous phases in structural and metallic glasses, attributed to the polyamorphism phenomena. Cusp in temperature dependences of ac magnetic susceptibility of weakly disordered LaMnO3 single crystal is registered below the temperature of magnetic ordering. Frequency dependence of the cusp temperature proves its spin-glass origin. The transition induced by a magnetic field in spin-glass state, is manifested by peculiarity in dependence of cusp temperature on applied magnetic field. Field dependent maximum of heat capacity is observed in the same magnetic field and temperature range.